The Welfare Impact of Global Migration in OECD Countries - Frédéric Docquier; Amandine Aubry; Michal Burzyński (Fondation pour les études et recherches sur le développement international (FERDI), 2016)
This paper quantifies the effect of global migration on the welfare of non-migrant OECD citizens. We develop an integrated, multi-country model that accounts for the interactions between the labor market, fiscal, and market size effects of migration, as well as for trade relations between countries. The model is calibrated to match the economic and demographic characteristics of the 34 OECD countries and the rest of the world, as well as trade flows between them in the year 2010. We show that recent migration flows have been beneficial for 69 percent of the non-migrant OECD population, and for 83 percent of non-migrant citizens of the 22 richest OECD countries. Winners are mainly residing in traditional immigration countries; their gains are substantial and are essentially due to the entry of immigrants from non OECD countries. Although labor market and fiscal effects are non-negligible in some countries, the greatest source of gain comes from the market size effect, i.e. the change in the variety of goods available to consumers.
Keywords: C68; F22; J24; 330